PENGARUH VARIETAS DAN LAMA FERMENTASI TERHADAP KUALITAS KEFIR SUSU KACANG TANAH (Arachis hypogaea) - Klaudia Maris Stella (BiSTeK Pertanian, 2019)
Kefir is one fermented product that has a taste, a yogurt-like consistency color and has a distinctive yeast aroma. Peanuts are economically ranked second after soybeans. As peanut food has important nutritional benefits in the human nutriency of high protein, minerals and essential fatty acids such as linoleic and oleic acids. Peanut milk contains a very high amino acid almost equivalent to the protein content of animal milk and the price is relatively cheap This study aims to determine the effect of varieties and length of fermentation on the quality of peanut milk kefir. The research design used was Completely Randomized Design (RAL) consisting of 2 factor V peanut varieties consisting of 2 levels (Hypoma 1 and Singa) and long L fermentation factor consisting of 3 levels (21, 24 and 27 hours), each of which was repeated 3 times. The observed observations were pH, total acid, alcohol content, protein content, fat content, Total Plate Count (TPC), Texture Profile Analysis (TPA). Treatment of varieties and duration of fermentation of peanut milk kefir have significant effect on pH value, total acid, fat content, Total Plate Count (TPC), significantly affect alcohol content and no significant effect on protein content, Texture Profile Analysis (TPA), organoleptic aroma, taste and texture. Quality of peanut milk kefir produced on lion varieties with 24 hours fermentation time of total acid 6.43%, alcohol content 2.84%, protein content 2.80%, Total Plate Count (TPC) 30.67 x 103 CFU and Adhesiveness 1.324 g/s.Keywords: Kefir, Long fermentation, Variety.